Synthesis, characterization, and mechanical and dynamic mechanical studies of β-alanine trimer-grafted SBR. (31st January 2018) - Zhao, Yihong; Fu, Lin; Jia, Li
Abstract: Two β-alanine trimer-grafted SBRs with varied grafting densities, 3a and3b, have been synthesized. The grafting density of3b is about twice of that of3a . FT-IR and DSC evidences suggest that the β-alanine trimer segments in both3a and3b exist exclusively in the β-sheet secondary structure, and the β-sheets stack to form crystals in the continuous SBR phase. The Tm of the β-sheet crystals in3b is higher than the Tm of those in3a . This likely suggests that the size of the crystals is somewhat larger in3b than in3a . TEM revealed that the β-sheet crystals are rod-like, with lengths on the order of a few tens of nanometers and widths of a few nanometers. The aspect ratio is much lower than that of the β-sheet crystals in segmented TPEs. The most prominent difference in the tensile behavior between3a and3b is strain hardening. The former is devoid of strain hardening, while the latter displays strong strain hardening. Overall, the high β-alanine content in3b leads to improvement of stiffness, ultimate strength and overall toughness at the sacrifice of extensibility and elastic recovery compared to3a . Dynamic mechanical studies showed that both3a and3b display very low loss factors, typical for TPEs with monodisperse hard segments that form β-sheet crystals, at temperatures up to 105 °C. Graphical abstract: Highlights: β-Alanine trimer grafted SBRs with different grafted densities have been synthesized and studied. The β-alanine segments form β-sheet crystals in the continuous SBR phase. The β-sheet crystals are several tens of nanometers long and several nanometers wide. Increase in grafting density improves stiffness, strength, and toughness but decreases extensibility and elastic recovery. Strain hardening is absent when the grafting density is low and present when high.